Performance of high-strength concrete walls exposed to fire. Issue 8 (June 2018) - Nguyen, Kate TQ; Ngo, Tuan; Mendis, Priyan; Heath, David
High-strength concrete is becoming very popular around the world due to its many advantages over normal-strength concrete. There are significant behavioural differences between high-strength concrete and normal-strength concrete, most notably the brittleness and sudden spalling under elevated temperatures, whereby pieces of hardened concrete explosively dislodge. Although all high-rise and even many medium-rise buildings have high-strength concrete walls, the spalling of high-strength concrete walls in fire has generally been ignored by the designers and the fire resistance of walls has been calculated using the rules specified for normal-strength concrete. Catastrophic failures could occur due to this ignorance of an important issue. Major design codes including the American and Australian Codes do not cover spalling adequately. Even the Eurocode rules are based on limited research. After a brief discussion on the present design practice, this article presents a summary of spalling research. The relevant results from a comprehensive study conducted at the University of Melbourne are briefly discussed. The authors are not aware of any other comprehensive research projects covering the fire behaviour of normal-strength concrete and high-strength concrete walls exposed not only to standard fires but also hydrocarbon fires. The results showed that spalling in high-strength concrete is more significant when subjected to hydrocarbon fire compared to normal-strength concrete. The level of compressive load on the panels was also found to have a significant effect on the fire performance of the high-strength concrete panels. The finite analysis element program, ANSYS, was used to model the concrete walls subjected to load and fire (both ISO834 Standard fire and hydrocarbon fire). The test results were used to validate the computer model.